Bounds on the Non‐real Spectrum of a Singular Indefinite Sturm‐Liouville Operator on ℝ. Issue 1 (October 2016) - Behrndt, Jussi; Schmitz, Philipp; Trunk, Carsten
Abstract: A simple explicit bound on the absolute values of the non‐real eigenvalues of a singular indefinite Sturm‐Liouville operator on the real line with the weight function sgn(·) and an integrable, continuous potential q is obtained. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)